Effect of Ag-doped on electrical transport properties in Pr0.75Na0.25MnO3 manganites - Khairulzaman, Nurul Nasuha; Shamsuddin, Suhadir; Ibrahim, Norazila (Institute of Advanced Scientific Research, 2020)
The monovalent doped Pr0.75Na0.25-yAgyMnO3 (y = 0 – 0.10) manganites have been investigated by DC electrical resistivity to elucidate the influence of Ag-doped on the electrical transport properties. The electrical resistivity measurement shows that the y = 0 sample exhibits insulating behaviour from 300 K down to 50 K. A similar behaviour was also shown for y = 0.10 sample. However, a metal insulator transition temperature, TMI was observed at 110 K for y = 0.05 sample suggestively due to the revival of double-exchange (DE) mechanism as a result of weakening the Jahn-Teller effect in the compound. Apart from that, the resistivity behaviour at temperature region above the TMI for y = 0 – 0.10 samples were found to fit well with the variable range hopping model with the increasing of hopping and activation energy as the Ag concentration increased suggested due to the distortion of MnO6 octahedral. Whilst for the metallic region which is below the TMI, the resistivity data of y = 0.05 sample was fitted well with the combination of domain/grain boundary, electronelectron and electron-magnon scattering. As for that, the impact of Ag+ ions doped on Pr0.75Na0.25MnO3 shows the significant results on the electrical transport properties.